Identifying Factors Influencing Recreational Travel during the COVID-19 Pandemic - Thapa, Diwas; Mishra, Sabyasachee; Dey, Kakan; Golias, Mihalis; Ashraf, Md Tanvir (My University, 2022)
This study aims to identify the psychological constructs that are antecedents to people's intention to travel to a tourist destination during the COVID-19 pandemic using the extended theory of planned behavior (ETPB) and necessary condition analysis (NCA). Online survey responses collected from 1,259 participants in the United States in May-June 2021 are used for the study. We find a moderating effect of public trust towards the government on the relationship between travel concerns and intentions. Results suggest that certain levels of public trust, subjective norm, perceived benefit of travel, perceived behavioral control, and perceived knowledge of the pandemic are necessary to manifest travel intentions. We uncover that providing travel incentives and better dissemination of the pandemic-related information can potentially encourage people to regain their original travel intention that was lost due to the pandemic. Furthermore, the bottlenecks obtained using NCA show that travel intentions are more easily manifested by perceived knowledge of the pandemic versus others. This study demonstrates the application of NCA, which can be further extended to make policy-level decisions for transportation systems.